2022
DOI: 10.1111/josh.13249
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Among Asian American Youth Before and During the COVID‐19 Pandemic

Abstract: PURPOSE:Early in the COVID-19 pandemic, there was a concern that cyberbullying incidents would increase as youth were spending more time online. Additionally, reports emerged that Asian American citizens were being disproportionately targeted due to the purported origination of the disease. The current study explores whether cyberbullying incidents increased among adolescents overall-and Asian American youth in particular-since the onset of the coronavirus. METHODS:Three unique national surveys of teens (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Participants also reported that other people physically distanced themselves farther than the amount recommended by public health authorities, which made them feel as if they were sick or as though they were the virus itself. It is also notable that some of the women described online encounters with such experiences; this corroborates other research during this period [ 10 , 29 ]. Studies have also reported that online victimization shot up alarmingly during the COVID-19 pandemic and negatively affected AAs’ mental health [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Participants also reported that other people physically distanced themselves farther than the amount recommended by public health authorities, which made them feel as if they were sick or as though they were the virus itself. It is also notable that some of the women described online encounters with such experiences; this corroborates other research during this period [ 10 , 29 ]. Studies have also reported that online victimization shot up alarmingly during the COVID-19 pandemic and negatively affected AAs’ mental health [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…On return to in‐person schooling, bullying re‐escalated to near pre‐pandemic levels 21 . Despite K‐12 students having an increased online presence during distance learning, measures suggest cyberbullying did not substantially increase during distance learning 21–23 . Through decreased rates of bullying, the pandemic may have had some indirect positive effects on certain aspects of student well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cyberbullying incidents raised along the COVID-19 (Barlett et al, 2021). The study with Asian American youth most likely to report increased victimization during the COVID-19 (Patchin & Hinduja, 2022). In Portugal, most participants (61%) reported experiencing cyberbullying during COVID-19 lockdowns (António et al, 2023).…”
Section: Prevalence Of Traditional Bullying and Cyberbullyingmentioning
confidence: 95%